The Tutsi genocide and transgenerational transmission of maternal stress: epigenetics and biology of the HPA axis. (May 2014) - Perroud, Nader; Rutembesa, Eugene; Paoloni-Giacobino, Ariane; Mutabaruka, Jean; Mutesa, Léon; Stenz, Ludwig; Malafosse, Alain; Karege, Félicien
Abstract: Objectives. Transmission of parental post-traumatic stress disorder (PTSD) to offspring might be explained by transmission of epigenetic processes such as methylation status of the glucocorticoid receptor (GR) gene ( NR3C1 ). Methods. We investigated PTSD and depression severity, plasma cortisol, GR and mineralocorticoid receptor (MR) levels, and methylation status of NR3C1 and NR3C2 promoter regions in 25 women exposed to the Tutsi genocide during pregnancy and their children, and 25 women from the same ethnicity, pregnant during the same period but not exposed to the genocide, and their children. Results. Transmission of PTSD to the offspring was associated with transmission of biological alterations of the HPA axis. Mothers exposed to the genocide as well as their children had lower cortisol and GR levels and higher MR levels than non-exposed mothers and their children. Moreover, exposed mothers and their children had higher methylation of the NR3C1 exon 1F than non-exposed groups. Finally, exposed mothers showed higher methylation of CpGs located within the NR3C2 coding sequence than non-exposed mothers. Conclusions. PTSD was associated with NR3C1 epigenetic modifications that were similarly found in the mothers and their offspring, modifications that may underlie the possible transmission of biological alterations of the HPA axis.